ONLINE-BASED SCIENCE PROJECT LEARNING AS AN ELECTIVE INSTRUCTING MODEL TO IMPROVE THE COLLABORATIVE SKILLS OF ELEMENTARY STUDENTS - Naila, Ishmatun; Kusumajanti, Wahju; Ridlwan, Muhammad; Sutadji, Eddy; Mashfufah, Aynin (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
In the era of Intelligent Society 5.0, collaborative skills, which can be defined as the ability to work effectively with others to achieve common goals, are essential competencies for students to thrive. Therefore, this study aims to explore the effectiveness of Online-based Science Project Learning (SPL) as a substitute instructional model for fostering collaborative skills among elementary school students. The study participants consisted of 75 elementary school fifth-grade students, distributed across three classes in Muhammadiyah Islamic Elementary School, Surabaya, East Java, Indonesia. It is important to comprehend that this examination was a replica of a preliminary test, and was conducted following the same methodology without the inclusion of a control group. The study design utilized a single-group approach, incorporating both a pretest and a posttest assessment. Furthermore, data analysis was conducted through paired t-test, n-gain calculation, and ANOVA using IBM SPSS version 25. The obtained results showed a statistically significant increase in the collective proficiency score of the observed students, as assessed at a 5% alpha level, after their engagement with the online-based Science Project Learning (SPL) model. Additionally, the average n-gains for the three grades were high, with no grade-level differences, and over 90% of the students responded positively to the online-based SPL Model teaching method. Based on these findings, it was concluded that online-based SPL models improved the collaborative work skills of the observed students. This study has several implications. First, it enhances the understanding of 21st-century life skills and abilities among elementary school teachers in Indonesia. Second, it suggests the potential for expanding the scope of the subject matter. Third, it underscores the importance of government collaborations in studies that prioritize the development of 4C skills, particularly collaboration, among students. Moreover, the study also emphasizes the necessity of online-based Science Project Learning (SPL) for scholars interested in remote learning, with a focus on examining the collaborative abilities and science learning outcomes of elementary students in virtual learning environments.